2010
DOI: 10.19030/jber.v8i3.692
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis: The Impact Of Non-Operating Revenues On Financial Viability Of Urban And Rural Hospitals

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="color: #0d0d0d; font-size: 10pt;"><span style="font-family: Times New Roman;">Fifty New York hospitals, 25 urban facilities and 25 rural facilities, were chosen at random for analysis.<span style="mso-spacerun: yes;">&nbsp; </span>They were examined to determine whether non-operating revenue &ndash; contributions, gifts, grants (as defined by IRS, Form 990) &ndas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These values are comparable to data from a few states in the United States that report values between 1% and 4%. 11,12,15 Additionally, dependence on NOR among rural hospitals demonstrates substantial variability with large standard deviations (4.1%-5.8%) and a heavy right skew. This finding is consistent with other studies that also observe significant variations in the mean proportion of NOR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These values are comparable to data from a few states in the United States that report values between 1% and 4%. 11,12,15 Additionally, dependence on NOR among rural hospitals demonstrates substantial variability with large standard deviations (4.1%-5.8%) and a heavy right skew. This finding is consistent with other studies that also observe significant variations in the mean proportion of NOR.…”
Section: Discussionmentioning
confidence: 99%
“…One study of 50 New York hospitals between 2005 and 2007 showed that urban hospitals had a higher median NOR than rural hospitals. 15 Another study in the 1980s described an intervention on rural hospitals based in the Northwest region, which found that a few hospitals were able to boost their negative operating margin to a total positive margin after including NOR. 16 A 2018 study showed that NOR sources were important to cover losses experienced when participating in value-based purchasing programs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations